For the function f, of, x, equals, start fraction, cube root of, x, end cube root, minus, 7, divided by, 5, end fractionf(x)=

5
3

x

−7

, find f, to the power minus 1 , left parenthesis, x, right parenthesisf
−1
(x).
Answer
Attempt 1 out of 2
Multiple Choice Answers
f, to the power minus 1 , left parenthesis, x, right parenthesis, equals, 5, x, cubed, plus, 7f
−1
(x)=5x
3
+7
f, to the power minus 1 , left parenthesis, x, right parenthesis, equals, 5, left parenthesis, x, plus, 7, right parenthesis, cubedf
−1
(x)=5(x+7)
3

f, to the power minus 1 , left parenthesis, x, right parenthesis, equals, left parenthesis, 5, left parenthesis, x, plus, 7, right parenthesis, right parenthesis, cubedf
−1
(x)=(5(x+7))
3

f, to the power minus 1 , left parenthesis, x, right parenthesis, equals, left parenthesis, 5, x, plus, 7, right parenthesis, cubedf
−1
(x)=(5x+7)
3

1 answer

To find the inverse function \( f^{-1}(x) \) for the given function \( f(x) = \frac{\sqrt[3]{x} - 7}{5} \), we need to follow these steps:

  1. Replace \( f(x) \) with \( y \): \[ y = \frac{\sqrt[3]{x} - 7}{5} \]

  2. Swap \( x \) and \( y \): \[ x = \frac{\sqrt[3]{y} - 7}{5} \]

  3. Solve for \( y \):

    • Multiply both sides by 5: \[ 5x = \sqrt[3]{y} - 7 \]
    • Add 7 to both sides: \[ 5x + 7 = \sqrt[3]{y} \]
    • Cube both sides: \[ (5x + 7)^3 = y \]
  4. Write the inverse function: \[ f^{-1}(x) = (5x + 7)^3 \]

Now, let's check the available options:

  1. Option 1: \( f^{-1}(x) = 5x^3 + 7 \)
  2. Option 2: \( f^{-1}(x) = 5(x + 7)^3 \)
  3. Option 3: \( f^{-1}(x) = (5(x + 7))^3 \)
  4. Option 4: \( f^{-1}(x) = (5x + 7)^3 \)

The correct option is: \[ f^{-1}(x) = (5x + 7)^3 \] which corresponds to Option 4.